2021
DOI: 10.1029/2021jb022546
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Patterns in Frictional Behavior of Sediments Along the Kumano Transect in the Nankai Trough

Abstract: Megathrust earthquakes at subduction margins induce hazardous ground motion and tsunami. The Nankai Trough, where the Philippine Sea plate subducts beneath the Amurian microplate offshore SW Japan at a convergence rate of 4.0-6.0 cm/yr (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 117 publications
(245 reference statements)
3
7
1
Order By: Relevance
“…Previous experimental studies have shown that volcanic glass has friction coefficients of 0.6-0.8 at low velocity conditions less than 1 mm/s (Lavallée et al, 2014;Wiemer & Kopf, 2015), consistent with "Byerlee's rule" for rock friction (Byerlee, 1978). When it is mixed with smectite, the frictional strength of the glass-smectite mixture shows an inverse relationship with smectite content (Wiemer & Kopf, 2015), similar to other previous results where weak clay minerals have been mixed with non-clay minerals (Bedford et al, 2022;Ikari et al, 2018;Logan & Rauenzahn, 1987;Okuda et al, 2021;Takahashi et al, 2007;Tembe et al, 2010). At a high slip-velocity up to 1.3 m/s, the frictional strength of volcanic glass is dynamically weakened (Lavallée et al, 2014).…”
Section: Introductionsupporting
confidence: 87%
“…Previous experimental studies have shown that volcanic glass has friction coefficients of 0.6-0.8 at low velocity conditions less than 1 mm/s (Lavallée et al, 2014;Wiemer & Kopf, 2015), consistent with "Byerlee's rule" for rock friction (Byerlee, 1978). When it is mixed with smectite, the frictional strength of the glass-smectite mixture shows an inverse relationship with smectite content (Wiemer & Kopf, 2015), similar to other previous results where weak clay minerals have been mixed with non-clay minerals (Bedford et al, 2022;Ikari et al, 2018;Logan & Rauenzahn, 1987;Okuda et al, 2021;Takahashi et al, 2007;Tembe et al, 2010). At a high slip-velocity up to 1.3 m/s, the frictional strength of volcanic glass is dynamically weakened (Lavallée et al, 2014).…”
Section: Introductionsupporting
confidence: 87%
“…The obtained μ showed a landward increasing trend such that it is 0.16-0.35 beneath the outer prism and 0.35-0.44 beneath the inner prism along the plate boundary zone (Figure 6b). Such a landward increasing trend of friction coefficient was also inferred by the Coulomb wedge model combining the prism topography with frictional strength of core samples from the accretionary prism, which did not include any a priori mineralogical variations (Okuda et al, 2021). They proposed that the μ at the trench-ward portion along the plate boundary beneath the outer prism is 0.24 (Ikari et al, 2013), and that the μ increases to 0.5-0.6 near the boundary between the outer and inner prisms, and to 0.6-0.8 at the updip limit depth of seismogenic zone.…”
Section: Spatial Variation In Frictional Strengthmentioning
confidence: 84%
“…Based on these studies, the previous study (Okuda et al, 2021) assumed the λ along the bottom of accretionary prism (=λb) to be 0.5 beneath the prism toe, 0.7 at the trench-ward part beneath the outer prism, 0.9 at the landward part beneath the outer prism, and 0.8 beneath the inner prism. Nearly hydrostatic pore pressure conditions were assumed inside the prism (λ = 0.5).…”
Section: Inference On Pore Pressure Conditionmentioning
confidence: 99%
“…Despite the clay-rich nature of the Nankai Trough sediments, velocity-weakening friction has been observed in other friction studies testing materials from this subduction zone, and specifically from the modern outer accretionary prism (Tsutsumi et al 2011;Roesner et al 2020;Okuda et al 2021). Although an earlier study found only velocity-strengthening friction for the megasplay (Ikari and Saffer 2011), this was later attributed to testing at higher than in situ stresses (Roesner et al 2020).…”
Section: Mechanisms Of Observed Behavior and Comparison With Previous...mentioning
confidence: 86%